1983
DOI: 10.1111/j.1755-3768.1983.tb01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Injection of Chalazia

Abstract: Corticosteroid (triamcinolone acetonide) injection of chalazion intralesionally is an effective, easy and a safe method. Perfect recovery was achieved in 88% of 24 chalazion cases (22 patients). Most of them were cured with a single injection. The steroid therapy is most effective when the chalazion has not been secondarily infected. If this has already happened surgery is the method of choice. If the steroid injections are limited only to common non-infected chalazia, the results will be excellent in about 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Jacky W. Y. Lee et al, compare in there study the effect of Intralesional Triamcinolone Acetonide Injection for Primary Chalazion in Children and Adults found that a single injection of intralesional TA for the treatment of primary chalazion was equally effective in children and adults, without any significant complications, and the rate of clinical response did not appear to be dose-dependent.in our study all patients were adult and we have reached to the same conclusion regarding the influence of chalazion size and triamcinolone used dose in treatment procedure [2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 60%
“…Jacky W. Y. Lee et al, compare in there study the effect of Intralesional Triamcinolone Acetonide Injection for Primary Chalazion in Children and Adults found that a single injection of intralesional TA for the treatment of primary chalazion was equally effective in children and adults, without any significant complications, and the rate of clinical response did not appear to be dose-dependent.in our study all patients were adult and we have reached to the same conclusion regarding the influence of chalazion size and triamcinolone used dose in treatment procedure [2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 60%
“…Serious complications of steroid injections, including skin depigmentation, fundus vascular occlusion, post-injection hemorrhage and inadvertent globe penetration, are rare 42 45 . Surgical incision may be suitable for large or infected chalazion or lesions that do not respond to conservative treatment 46 . However, permanent eyelid dysfunction and aesthetic flaws may arise from eyelid marginal and numerous incisions for recurring chalazion.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 The choice of treatment of chalazion is usually based on clinical experience as was observed in this study, but it is important to note that the cytopathologic appearance of the chalazion granuloma, whether it is a mixed cell or a suppurating type, may also determine the choice of 4, 9 treatment. 4,16 Chalazion can be treated conservatively using an intralesional injection of long-acting corticosteroid, 17,18,19 surgery in the form of incision and curettage or 13 subconjunctival total excision of the chalazion or a 20 combination of surgery with intralesional injection. In our 4,16 centre, incision and curettage are the standard methods of treatment and these were administered in 74.6% of the cases.…”
Section: Discussionmentioning
confidence: 99%